Negotiating better teamwork. Part one, general instruction - Collins, William, active 2024; Yue, Tao, active 2024 (London : Rotterdam School of Management, Erasmus University, 2024)
Lee, a member of an MBA program team facing interpersonal challenges, takes a contemplative walk to prepare for a tough conversation with an underperforming team member. The team, formed just three months ago, struggles with internal conflicts, and Lee believes addressing this issue early is essential for future success. He embraces this opportunity to develop leadership skills by providing clear feedback, active listening, seeking constructive solutions, focusing on behavior rather than personality, and managing emotions without judgment.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Teams in the workplace -- Case studies